Development of web-based learning multimedia to improve students understanding of mathematical concepts in elementary schools - Runniarsiti, Runniarsiti; Arismunandar, Arismunandar; Febriati, Farida (Journal of Research in Instructional, 2025)
Rapid technological advances in education have increased student engagement, but some schools still struggle with optimal understanding of mathematical concepts, which impacts learning outcomes. The purpose of this study was to create and evaluate web-based learning multimedia that can improve students' understanding of mathematical concepts. We conducted research and development involving fourth-grade elementary school students. A small-scale trial with six students aimed to observe student responses to the use of web-based learning multimedia in mathematics. Meanwhile, large-scale trials were conducted in three elementary schools with a total of 69 students. Validation involved media and design experts as well as material experts. Data were analyzed quantitatively using percentages and the Wilcoxon test. Interview results revealed a conventional learning process with minimal student participation and limited use of technology. Students tended to be more interested in the use of interactive media, such as videos and images, in the learning process. The results of media validation showed a very good validity level (96.25%), and material validation also showed a very high validity level (90.1%). The measurement results showed that teachers and students responded well, with a percentage above 80%. It indicates that the web-based learning multimedia is very practical. Effectiveness analysis indicates that the developed product effectively improves elementary school students' understanding of mathematical concepts (sig. < 0.05). This study concludes that the developed product, namely web-based learning multimedia, meets the standards of validity, practicality, and effectiveness in improving elementary school students' understanding of mathematical concepts.